2019
DOI: 10.1371/journal.pone.0214678
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of mental health recovery narratives: Systematic review and narrative synthesis

Abstract: Background Narratives of recovery from mental health distress have played a central role in the establishment of the recovery paradigm within mental health policy and practice. As use of recovery narratives increases within services, it is critical to understand how they have been characterised, and what may be missing from their characterisation thus far. The aim of this review was to synthesise published typologies in order to develop a conceptual framework characterising mental health recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
134
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 96 publications
(135 reference statements)
11
134
0
4
Order By: Relevance
“…Whereas others clearly positioned improvements in mental health as occurring within DES. People may also follow different non-linear trajectories of recovery and see themselves at different stages of their journey (recovered, living well, making progress or surviving day-to-day) [69]. This was also evident in the emerging narratives, with some participants reflecting positive trajectories across all CHIME components, with others describing oscillating experiences.…”
Section: Qualitative Narrative Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Whereas others clearly positioned improvements in mental health as occurring within DES. People may also follow different non-linear trajectories of recovery and see themselves at different stages of their journey (recovered, living well, making progress or surviving day-to-day) [69]. This was also evident in the emerging narratives, with some participants reflecting positive trajectories across all CHIME components, with others describing oscillating experiences.…”
Section: Qualitative Narrative Analysismentioning
confidence: 96%
“…Ridgway [68] for example used first person narratives to explore lived experiences of recovery of women with long-term psychosocial disability, describing how these narratives could inform recovery-orientated practice. Whilst a recent systematic review of mental health recovery reported on 45 separate studies documenting personal recovery narratives, demonstrating the wide utilisation of narrative inquiry to understand perspectives of recovery [69].…”
Section: Qualitative Narrative Analysismentioning
confidence: 99%
“…Therefore, the unity of human life [117] can be seen as broken [33,72] and the coherence of the self as disturbed [118] in conditions resulting from traumatic events. However, in the context of recovery therapy [119], this should not be seen as an irresolvable situation, and it is necessary to create another narrative or fiction that "works" [19] to create meaning out of the traumatic event and to include it with consistency in one's life story.…”
Section: Seeing Psychological Trauma As a Break In The Narrative Andmentioning
confidence: 99%
“…Mental health recovery narratives are first-person lived experience accounts of recovery from mental health problems, which include elements of adversity or struggle and of selfdefined strengths, successes or survival [1]. They have been described as a "key recovery technology" [2], central to the recovery approach within mental health policy and practice [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite wide-ranging use in mental health practice, and the possibility of creating both benefits and harms, there has been a lack of conceptual clarity and consistency in the definition of recovery narratives [1]. A clearer understanding of their characteristics could ensure that future use of narratives in clinical interventions and practice provide maximum benefit and minimum harms to recipients.…”
Section: Introductionmentioning
confidence: 99%